Sympathetic ophthalmia after 23-gauge transconjunctival sutureless vitrectomy - Masatoshi Haruta (Dove Medical Press, 2010)
Masatoshi Haruta1, Hirokazu Mukuno2, Kazuaki Nishijima3, Hitoshi Takagi4, Mihori Kita51Department of Ophthalmology, Kurume University School of Medicine, Kurume, Fukuoka, Japan; 2Department of Ophthalmology, Konan Hospital, Kobe, Hyogo, Japan; 3Department of Ophthalmology and Visual Sciences, Kyoto University Graduate School of Medicine, Kyoto, Kyoto, Japan; 4Department of Ophthalmology, St Marianna University School of Medicine, Kawasaki, Kanagawa, Japan; 5Department of Ophthalmology, Hyogo Prefectural Amagasaki Hospital, Amagasaki, Hyogo, JapanPurpose: We report a case of a sympathetic ophthalmia that occurred after 23-gauge transconjunctival sutureless vitrectomy for a retinal detachment.Case report: A 41-year-old Japanese woman underwent combined phacoemulsification with intraocular lens implantation and 23-gauge transconjunctival sutureless vitrectomy for a rhegmatogenous retinal detachment in the right eye. Endolaser photocoagulation and silicone oil tamponade were used to manage inferior retinal holes. Four weeks after the surgery, she returned with a 5-day history of reduced vision and metamorphopsia in her left eye. Slit-lamp examination showed a shallow anterior chamber in the right eye and moderate anterior uveitis bilaterally. Silicone oil bubbles and pigment dispersion were observed in the subconjunctival space adjacent to the right eye’s superonasal sclerotomy site. Fundus examination showed multifocal serous retinal detachments in both eyes. A diagnosis of sympathetic ophthalmia was made and the patient was treated with intensive topical and systemic steroids. The subretinal fluid cleared in both eyes following treatment. Twelve months after the onset of inflammation, the patient’s condition was stable on a combination of oral cyclosporine and topical steroids. Sunset glow retinal changes remain, but there has been no evidence of recurrent inflammation.Conclusion: Sympathetic ophthalmia can develop after 23-gauge transconjunctival sutureless vitrectomy despite its smaller sclerotomy size. We recommend that special care should be taken to inspect for adequate closure of sclerotomy sites at the end of this operation.Keywords: fluorescein angiography, hypotony, optical coherence tomography, retinal detachment, shallow anterior chamber